Child-Centered Adjudication: Integrating the Best Interests Principle Into Indonesian Marital Property Distribution - Muchlis, Muchlis; Yasardin, Yasardin; Mukhlas, Oyo Sunaryo; Khosyi’ah, Siah; Al Hasan, Fahadil Amin (Nurani, 2025)
The division of marital property often presents a complex legal dilemma. Greater judicial evaluation usually considers acquisition timing, sources, and separation agreements. Nevertheless, the recent Indonesian jurisprudence, especially the Supreme Court Circular Letter (SEMA) No. 1/2022 and Cassation Decision No. 377 K/Ag/2023 (5 April 2023), requires the introduction of the principle of the best interests of a child, as stipulated in the Child Protection Act, to the adjudication of marital property. This study adopts a qualitative documentary analysis that draws upon primary legal sources, including statutes, circular letters, and court decisions, and is supplemented by secondary academic literature. The analysis demonstrates how normative rules and jurisprudence integrate the child’s best interest into post-divorce asset allocation. The results indicate that a child’s welfare has become a necessary pillar in judicial reasoning, influencing courts to postpone the distribution of marital assets until children reach adulthood. This normative and jurisprudential shift highlights not only legal enforcement but also substantive justice, ensuring children’s decent living conditions. This research contributes by elucidating the legal significance of Decision 377 K/Ag/2023, which reinforces the role of the best interests principle in Indonesian family law and advances a progressive approach to the adjudication of marital disputes.